Home Water Tank Monitoring - Adilah, Noor; Ahmad, Nur Zaimah (Journal of Computing Technologies and Creative Content, 2020)
Home Water Tank Monitoring is a prototype that can send data to the receiver using LoRa technology. The prototype used LoRa technology because it is a long range and low-cost technology. It shows the communication between the sender and receiver of LoRa technology and notify the user if the water level in the tank is below than 100 litres. A single point water sensor has been placed in the water tank and it will be triggered if the water level is below it. It then sends data to the receiver. As the data received by the receiver, it then displays the data using the serial monitor. Based on the data collected, the data transmitted between sender and receiver need less than three level building. Besides, data can be transmitted 60 Metres with barrier. For future enhancements, the system should be able to notify the user via SMS and keep data in database for analysis. The prototype is using Arduino, LoRa shield and sensor as main components. As a conclusion, LoRa technology work well with Arduino to make this system successful.